Modification of Sidoardo Lava Mud (“LUSI”) to Become Granular Material for Quality Fill Materials - D. Pasmar; N.E. Mochtar (Lowland Technology International, 2019)
The term LuSi is abbreviation of Lumpur Sidoarjo, which is a certain type of hot lava mud coming out from the earth in Sidoarjo, East Java, Indonesia. The hot lava mud initially was outflowing at the rate about 100.000m3/day and the flow peaked around 125.000m3/day in 2007, but then gradually decreasing to become 20.000m3/day up to now. LuSi contains of 88% fine materials with LL=81.58% and PI=49.56%; it is classified as CH or A-7-6. To reduce the volume of LuSi, it is planned to use as quality fill materials; it means that LuSi has to meet the fill material requirement. For this purpose, 10% of lime Ca(OH)2 used as stabilization material and granulation process adopted to modify its particle size. The new material produced is non-plastic material called as granular lime-stabilized LuSi (SGL); its grain size is affected by rotation speed of granulator drum (V) during the granulation process. If SGL is compacted using compaction energy 90% of the maximum dry density (MDD), the minimum values of soaked CBR obtained are 7%, 12%, and 13% for V=6rpm, 8rpm, and 10rpm, respectively. It shows that SGL can be used at least as “regular fill material” because its minimum soaked CBR>6%.